An ANTI-CORRUPTION EDUCATION IN THE NATIONAL CURRICULUM - Adya Winata, Koko; Supriyadi, Asep; Ihsan, Mahlil; Ismail, Shalahudin (Qawwam : The Leader's Writing, 2025)
Corruption is a chronic problem that can hinder development and damage the order of national life. Efforts to eradicate it cannot rely solely on legal approaches, but must be accompanied by preventive strategies through education. Anti-corruption education is seen as a strategic effort that is urgently needed to build values of honesty, integrity, responsibility, and justice. By fostering anti-corruption character through anti-corruption education in schools, it is hoped that a society will emerge that has the moral resilience and courage to reject corruption in all its forms. This article examines anti-corruption education in the national curriculum. The research method used a conceptual and normative approach through literature review and analysis of education policy. The results of the discussion show that anti-corruption education is relevant to the national education goal of developing students who are faithful, have noble character, are intelligent, and are responsible. Anti-corruption values can be implemented in schools through three approaches, namely integration into subjects, strengthening an open and accountable school culture, and participatory and extracurricular activities. Anti-corruption education in the national curriculum is urgently needed to shape a society that is honest, strong in character, transparent, and free from corruption.